Graphene based inks for printed electronics - Xiang, Wenjun (Kansas State University, 2021)
The outstanding properties of graphene make it attractive to be used as a conductive filler in inks that play an important role in printed electronics. In this thesis, liquid-phase exfoliation of pristine graphite, with the addition of ethyl cellulose stabilizer in ethanol, is employed to prepare high concentration graphene dispersions. Subsequently, the exfoliated graphene nano-flakes were collected and redispersed in cyclohexanone/terpineol solvent to form inks which were successfully inkjet printed on flexible polyimide substrates. The ideal synthesis conditions for the yielding of high concentration graphene inks including the concentration of surfactants (C), sonication time (t) and sonication energy (E) were examined. Ultraviolet–visible spectroscopy (UV-Vis) and electrical resistance were performed on the ink to show optimized results. Graphene-graphene aerosol gel (Graphene-GAGs) and graphene-multi-walled carbon nanotubes (Graphene-MWCNTs) hybrid inks, based on the optimized ink, were successfully synthesized for inkjet printing. Compared with pure graphene devices, the graphene-graphene aerosol gel (Graphene-GAGs) and graphene-multi-walled carbon nanotubes (Graphene-MWCNTs) electrodes exhibited superior electrochemical performance as demonstrated by the cyclic voltammetry test with hexaammineruthenium(III) chloride, indicating their promising application in electrochemical sensors. While the use of synthesized graphene as a matrix compared well with commercial graphene ink, potential for further improvements remains open in this research field.
Keywords: Graphene; Conductive inks; Printed electronics